Influences of Combined Organic Fouling and Inorganic Scaling on Flux and Fouling Behaviors in Forward Osmosis - Youngpil Chun; Kwanho Jeong; Kyung Hwa Cho (Membranes, 2020)
This study investigated the influence of combined organic fouling and inorganic scaling on the flux and fouling behaviors of thin-film composite (TFC) forward osmosis (FO) membranes. Two organic macromolecules, namely, bovine serum albumin (BSA) and sodium alginate (SA), and gypsum (GS), as an inorganic scaling agent, were selected as model foulants. It was found that GS scaling alone caused the most severe flux decline. When a mixture of organic and inorganic foulants was employed, the flux decline was retarded, compared with when the filtration was performed with only the inorganic scaling agent (GS). The early onset of the conditioning layer formation, which was due to the organics, was probably the underlying mechanism for this inhibitory phenomenon, which had suppressed the deposition and growth of the GS crystals. Although the combined fouling resulted in less flux decline, compared with GS scaling alone, the concoction of SA and GS resulted in more fouling and flux decline, compared with the mixture of BSA and GS. This was because of the carboxyl acidity of the alginate, which attracted calcium ions and formed an intermolecular bridge.